Superdotação, transtorno de déficit de atenção/hiperatividade e dupla excepcionalidade um estudo de indicadores e habilidades sociais - Ogeda, Clarissa Maria Marques (Editora Oficina Universitária, 2020)
The book presents its readers with new ways to understand the phenomena of Giftedness and Attention Deficit/Hyperactivity Disorder. Through a rigorous methodological design, the author investigates the diagnosis of ADHD in subjects with gifted behavior, as well as Giftedness in subjects with ADHD, and expands discussions on the manifestation of dual exceptionality based on national and international theoretical references. KETILIN MAYRA PEDRO The book presents a discussion that is extremely necessary for the 21st century and brings reflections on the phenomena of Giftedness and Attention Deficit/Hyperactivity Disorder, outlining, demystifying and warning about the possibility of their co-occurrence - the so-called Dual Exceptionality -, which manifests itself in indicators of one and the other phenomenon, but, like every encounter, it transforms and presents specific indicators. The complexity and heterogeneity intrinsic to the groups can make it difficult to diagnose and work with these students, in different areas: family, school and society. Understanding them and meeting their needs is necessary for those who dedicate themselves to teaching, as they can become leaders who are more empathetic to human needs and promote the cultural and technological development of our society. With a multidisciplinary and multimodal approach, the indicators of the phenomena and their social skills are investigated, pointing out strengths and weaknesses, which can provide opportunities for understanding in the face of such a paradoxical, dynamic reality with apparently contradictory traits.